Business Negotiation Strategies: A Study of English Persuasive Communication in Decision-Making Processes - Nurwahida Nurwahida; Rahmiati Rahmiati; Ratnah Ratnah; Alfiana Damasinta (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
English has become the lingua franca in international business negotiations, which means that English persuasive communication is an important element for decision making. This study analyzes how English persuasive strategies shape negotiation outcomes, identifies key linguistic and pragmatic elements that contribute to negotiation success, and explores contextual factors that influence communicative effectiveness in various business settings. Adopting a descriptive qualitative literature review, this paper synthesizes insights derived from international studies on communication, negotiation and business English. The results indicate that the ability to structure logical arguments, present data-driven claims, use culturally sensitive discourse strategies, and manage interpersonal rapport in English significantly enhances negotiation effectiveness. In digital negotiation contexts, communicative clarity and adaptability become even more essential due to the reduced availability of non-verbal cues. Mastery of English persuasive communication not only improves agreement quality but also strengthens long-term business relationships and supports organizational competitiveness in global markets.